South china sea dispute: Way forward? - Singh, Anita (IIPA Digest)
As the name suggests, South China Sea (SCS) is located south of Chinese Mainland. It is huge water body with an area of 3.5 million km square. this area is under intense focus due to aggressive and overlapping claims made by China on others territorial waters. The growing interest in SCS is due to the discovery of oil and natural gas below the bed of SCS. it is also the hotbed for fishing industry as 12% of global fish catch comes from SCS. It is believed that there is 11 billion barrels of oil and 190 trillion cubic feet of natural gas is in the SCS. - Reproduced